1987
DOI: 10.1016/0014-5793(87)81361-3
|View full text |Cite
|
Sign up to set email alerts
|

The insulin receptor tyrosyl kinase phosphorylates holomeric forms of the guanine nucleotide regulatory proteins Gi and Go

Abstract: An affinity purified human insulin receptor preparation was shown to phosphorylate the LY-and B-subunits of the guanine nucleotide-regulatory proteins Gi and G,, derived from bovine brain. The presence of insulin stimulated the rate of their phosphorylation some 2-fold. The presence of Gi and G, did not affect the degree of autophosphorylation of the B-subunit of the insulin receptor. Under conditions known to cause the dissociation of G, and G, into their constituent subunits then phosphorylation of Gi and G,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(47 citation statements)
references
References 31 publications
(7 reference statements)
2
45
0
Order By: Relevance
“…Similarly, we [5] and others [6] have shown that incubation of pure preparations of Gi and Go with a purified human insulin receptor preparation leads to the phosphorylation of ce-Gi. It has been suggested that phosphorylation of Gi by protein kinase C may lead to its inactivation as incubation of platelets with tumour promoting phorbol esters, which activate protein kinase C, blocked the ability of CeE-adrenoceptors to inhibit adenylate cyclase activity [7].…”
Section: Introductionsupporting
confidence: 64%
“…Similarly, we [5] and others [6] have shown that incubation of pure preparations of Gi and Go with a purified human insulin receptor preparation leads to the phosphorylation of ce-Gi. It has been suggested that phosphorylation of Gi by protein kinase C may lead to its inactivation as incubation of platelets with tumour promoting phorbol esters, which activate protein kinase C, blocked the ability of CeE-adrenoceptors to inhibit adenylate cyclase activity [7].…”
Section: Introductionsupporting
confidence: 64%
“…These authors showed that insulin-dependent lipolysis and inhibition of glucose oxidation in adipocytes were blocked by pertussis toxin. Following this original observation, there were several reports that suggested that the insulin receptor phosphorylates G␣ i and G␣o (O'Brien et al, 1987;Krupinski et al, 1988) and that the insulin receptor is coupled to G proteins of the Gi family (Rothenberg and Kahn, 1988;Ciaraldi and Maisel, 1989). These studies were followed by reports of G proteins associated with the insulin receptor (Jo et al, 1992(Jo et al, , 1993 and the identification of regions within the insulin receptor that can activate heterotrimeric G proteins .…”
Section: B Insulin and Insulin-like Growth Factor Receptorsmentioning
confidence: 97%
“…Phosphorylation of G proteins by, for example, protein kinases C1C. W.Taylor C (Sagi-Eisenberg, 1989: Pyne et al, 1989 or receptor tyrosine kinases (Zick et al, 1986;Valentine-Braun et al, 1986;O'Brien et al, 1987) (Jakobs et al, 1985).…”
Section: G Proteins Remembermentioning
confidence: 99%